COMPARATIVE ANALYSIS OF TRAUMA REDUCTION TECHNIQUES IN LAPAROSCOPIC CHOLECYSTECTOMY - Anton Koychev; Svetoslav Garov; Tsvetelina Mihailova; Veselin Ilinov (Peytchinski Publishing, 2017)
Nowadays, there is no operation in the field of abdominal surgery, which cannot be performed laparoscopically. Both surgeons and patients have at their disposal an increasing number of laparoscopic techniques to perform the surgical interventions. The prevalence of laparoscopic cholecystectomy is due to its undeniable advantages over the traditional open surgery, namely small invasiveness, reducing the frequency and severity of perioperative complications, the incomparably better cosmetic result, and the so much better medical and social, and medical and economic efficiency. Single-port laparoscopic techniques to perform laparoscopic cholecystectomy are acceptable alternative to the classical conventional multi-port techniques. The security of the laparoscopic cholecystectomy requires precise identification of anatomical structures and precise observing the diagnostic and treatment protocols, and criteria for selection of patients to be treated surgically by these methods.